2022
DOI: 10.1155/2022/7427967
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation Model of Football Players’ Training and Teaching Actions Based on Artificial Intelligence

Abstract: Football is a sport that needs to combine the physical stamina and physical characteristics of athletes. It needs to pay attention to the differences in different individuals and then conduct targeted training. In this regard, this article introduces artificial intelligence technology into the teaching actions of football player training and analyzes the teaching elements according to the characteristics of the football player’s body. Through the analysis of fog computing under artificial intelligence, this ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Feng, Y et al investigated an artificial intelligence-based model for assessing soccer players' training and teaching behaviors. By collecting and analyzing soccer training and game video data, the authors combined machine learning and deep learning techniques to construct an assessment model that can evaluate soccer players at different levels and provide targeted training recommendations to help soccer coaches better guide their athletes' training and improve their competitive performance [11]. The literature [12] showed that a soccer training model based on game experience learning could improve youth soccer players' teamwork and respectful attitudes without compromising their skill and physical ability development.…”
Section: Introductionmentioning
confidence: 99%
“…Feng, Y et al investigated an artificial intelligence-based model for assessing soccer players' training and teaching behaviors. By collecting and analyzing soccer training and game video data, the authors combined machine learning and deep learning techniques to construct an assessment model that can evaluate soccer players at different levels and provide targeted training recommendations to help soccer coaches better guide their athletes' training and improve their competitive performance [11]. The literature [12] showed that a soccer training model based on game experience learning could improve youth soccer players' teamwork and respectful attitudes without compromising their skill and physical ability development.…”
Section: Introductionmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%